Costimulatory Blockade‐Induced Allograft Survival Requires Beclin1. Issue 3 (6th February 2014) - Verghese, D. A.; Yadav, A.; Bizargity, P.; Murphy, B.; Heeger, P. S.; Schröppel, B.
<x xml:space="preserve">Abstract</x> Autophagy is required for T cell homeostasis and activation‐induced T cell expansion. Whether autophagy participates in tolerance induction to foreign antigens, including allografts, is unknown. We tested the role of an essential autophagy protein, Beclin1, in heart transplant survival in mice. We observed that long‐term allograft survival induced by donor‐specific transfusion plus anti‐CD154 mAb required homozygous lymphocyte expression of Beclin1. Following adoptive transfer into allogeneic recipients, autophagy‐deficient, Beclin1 heterozygous effector T cells (Teffs) exhibited enhanced proliferation with diminished cell death and increased production of interferon gamma. Whereas the induction and function of regulatory T cells (Tregs) in Beclin1 heterozygous mice were normal, Teffs from these mice were resistant to Treg‐mediated suppression. Our findings identify a requisite role for Beclin1 in facilitating Teff death during tolerance induction.